2014
DOI: 10.1007/s12010-014-1039-3
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore as a Potential Plant Growth-Promoting Agent Produced by Pseudomonas aeruginosa JAS-25

Abstract: Siderophores scavenges Fe(+3) from the vicinity of the roots of plants, and thus limit the amount of iron required for the growth of pathogens such as Fusarium oxysporum, Pythium ultimum, and Fusarium udum, which cause wilt and root rot disease in crops. The ability of Pseudomonas to grow and to produce siderophore depends upon the iron content, pH, and temperature. Maximum yield of siderophore of 130 μM was observed at pH 7.0 ± 0.2 and temperature of 30 °C at 30 h. The threshold level of iron was 50 μM, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
2
34
0
2
Order By: Relevance
“…As expected, no colour change was observed in the uninoculated plates after incubation for 3 weeks. Similar finding have been reported by several workers [24,25]. Spectrophotometric analysis of the culture in standard succinate medium showed a peak between 420 to 450 nm (Fig.…”
Section: IIIsupporting
confidence: 91%
“…As expected, no colour change was observed in the uninoculated plates after incubation for 3 weeks. Similar finding have been reported by several workers [24,25]. Spectrophotometric analysis of the culture in standard succinate medium showed a peak between 420 to 450 nm (Fig.…”
Section: IIIsupporting
confidence: 91%
“…Several studies have found P. fluorescens, P. putida, P. aeruginosa, and Pseudomonas sp promoting the plant growth through the BNF, production of hormones, and siderophores in rice (Oryza sativa), rapeseed (Brassica napus L.), ginger (Zingiber officinale), corn (Zea mays L.), and sugarcane (Sarcarumm L.) (Sulochana et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Siderophores have also been reported to induce systemic acquired resistance (Trivedi et al, 2008; Sulochana et al, 2014). P. aeruginosa BRp3 produces 1-hydroxy-phenazine, pyocyanin (Figure 1) and pyochelin ( m/z 325, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa in the suppression of charcoal rot disease of chickpea. Different types of siderophores such as pesudobactin and pyoverdine produced by rhizospheric bacteria chelate to the available form of iron present in the soil and suppress the pathogens by reducing the availability of iron for the phytopathogen (Wensing et al, 2010; Sulochana et al, 2014). Notably, the number of rhizosphere-associated Pseudomonas species involved in yield enhancement (Combes et al, 2011) and/or reduction in plant diseases, are increasing (Couillerot et al, 2009; Beneduzi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%